9
$\begingroup$

This problem is taken from Algerian Olympiad and asks to prove that

$$\sum_{n=0}^{\infty} \dfrac{5^n(3^{5^{n+1}} -5\cdot3^{5^n} + 4)}{(729)^{5^n} - (243)^{5^n}-5\cdot3^{5^n}+1} = \frac 12.$$

Noticing that $729=3^6$ and $243 = 3^5$, I tried simplifying the general terms by setting $x=3^{5^n}$ but it seems to give no simplifications.

Thanks in advance for any advice / ideas.

$\endgroup$
  • 4
    $\begingroup$ WA shows that the sum is greater than $\frac12$. $\endgroup$ – Saad Mar 3 '18 at 4:16
  • $\begingroup$ D'oh. If anyone can find the actual sum, then I'll give them the bounty. :-P $\endgroup$ – Theo Bendit Mar 3 '18 at 4:55
  • $\begingroup$ Can anyone link the source for this? $\endgroup$ – Akababa Mar 3 '18 at 5:37
12
+100
$\begingroup$

I think the "$5 \cdot 3^{5^n}$" in the denominator is a typo and it can be proved that$$ \sum_{n = 0}^\infty \frac{5^n (3^{5^{n + 1}} - 5 \cdot 3^{5^n} + 4)}{3^{6 \cdot 5^n} - 3^{5^{n + 1}} - 3^{5^n} + 1} = \frac{1}{2}. $$

In fact,$$ \sum_{n = 0}^\infty \frac{5^n (3^{5^{n + 1}} - 5 \cdot 3^{5^n} + 4)}{3^{6 \cdot 5^n} - 3^{5^{n + 1}} - 3^{5^n} + 1} = \sum_{n = 0}^\infty \left( \frac{5^n}{3^{5^n} - 1} - \frac{5^{n + 1}}{3^{5^{n + 1}} - 1} \right) = \frac{5^0}{3^{5^0} - 1} = \frac{1}{2}. $$

| cite | improve this answer | |
$\endgroup$
  • 5
    $\begingroup$ +1 for what is most likely the right answer to a wrongly posed question. $\endgroup$ – dxiv Mar 3 '18 at 6:06
  • $\begingroup$ Hi, it's a copy paste from the officiel text, the error is in the original problem statement $\endgroup$ – Oussama Sarih Mar 3 '18 at 20:32
  • 2
    $\begingroup$ It's always harder when the problem is wrong. $\endgroup$ – marty cohen Mar 4 '18 at 2:48
5
$\begingroup$

The series does indeed converge (by the ratio test, for example), but its sum is not $\,\dfrac{1}{2}\,$, it is rather strictly greater than $\,\dfrac{1}{2}\,$. The first two terms add up to $\dfrac{29}{59}$ $+$ $\dfrac{529555380145}{25630480435499}$ $\simeq 0.512$ $\gt \dfrac{1}{2}\,$ already, and adding more positive terms will only increase the sum further.

To show that all terms are in fact positive, it is enough to note that with $\,x=3^{5^n} \ge 3\,$ both:

  • numerator $\,5^n(x^5-5x+4) = 5^n(x-1)^2(x^3+2x^2+3x+4) \ge 0$;

  • denominator $\,x^6-x^5-5x+1 = u^6 + 11 u^5 + 50 u^4 + 120 u^3 + 160 u^2 + 107 u + 23\ge 0\,$ where $\,u=x-2 \ge 0\,$.

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

The series is convergent but it does not converge to $0.5$.

This series has a high degree of convergence and it converges to $0.512186580754$ which is greater than $0.5$.

  • At $n=0$, the value is $0.491525423729$
  • At $n=1$, the value is $0.512186580724$
  • At $n=2$, the value is $0.512186580754$
  • At $n=3$, the value is $0.512186580754$

Here is a scatter diagram ,

enter image description here

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.